In Planta Synthesis of Designer-Length Tobacco Mosaic Virus-Based Nano-Rods That Can Be Used to Fabricate Nano-Wires - Saunders, Keith; Lomonossoff, George P. (Frontiers in Plant Science, 2017)
We have utilised plant-based transient expression to produce tobacco mosaic virus (TMV)-based nano-rods of predetermined lengths. This is achieved by expressing RNAs containing the TMV origin of assembly sequence (OAS) and the sequence of the TMV coat protein either on the same RNA molecule or on two separate constructs. We show that the length of the resulting nano-rods is dependent upon the length of the RNA that possesses the OAS element. By expressing a version of the TMV coat protein that incorporates a metal-binding peptide at its C-terminus in the presence of RNA containing the OAS we have been able to produce nano-rods of predetermined length that are coated with cobalt-platinum. These nano-rods have the properties of defined-length nano-wires that make them ideal for many developing bionanotechnological processes.